2019
DOI: 10.3122/jabfm.2019.02.180222
|View full text |Cite
|
Sign up to set email alerts
|

Reports of Two Broken Nexplanon® Rods

Abstract: Damage to progestin containing contraceptive implants has been reported for Implanon® rods but there appear to be few reports of damage to Nexplanon® rods. This report describes 2 cases of Nex-planon® rod breakage in an 18-year-old female and a 25-year-old female. The literature regarding damaged progestin implants is reviewed. These reports often involve an alteration in menstrual bleeding pattern and patients frequently request removal of bent or broken implants. The overall incidence of rod breakage and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In vitro studies have suggested that a broken or bent implant may release more etonogestrel than an intact one, and case reports have described increased vaginal bleeding after broken implants. These women did not become pregnant, but data are limited on the changes in efficacy after a broken rod, and we suggest shared decision-making with the patient and Ob/gyn regarding removal of a broken implant 10,45 …”
Section: Subdermal Implants—common Complications Evaluation and Manag...mentioning
confidence: 96%
See 1 more Smart Citation
“…In vitro studies have suggested that a broken or bent implant may release more etonogestrel than an intact one, and case reports have described increased vaginal bleeding after broken implants. These women did not become pregnant, but data are limited on the changes in efficacy after a broken rod, and we suggest shared decision-making with the patient and Ob/gyn regarding removal of a broken implant 10,45 …”
Section: Subdermal Implants—common Complications Evaluation and Manag...mentioning
confidence: 96%
“…These women did not become pregnant, but data are limited on the changes in efficacy after a broken rod, and we suggest shared decision-making with the patient and Ob/gyn regarding removal of a broken implant. 10,45 Pregnancy Pregnancy with implants is exceedingly rare. In a study of 7364 Nexplanon users, there were 12 pregnancies.…”
Section: Systemic Hormonal Effectsmentioning
confidence: 99%
“…A report of 2 such cases from the University of Arizona reviews the literature and offers clinical advice for other providers facing this dilemma. 14 Two well-done studies in this issue show that direct comparison of existing options often provides enlightening results. Tong et al 15 compare 2 tools that can be used to screen for prescription psychotherapeutic medication misuse.…”
mentioning
confidence: 99%